Pengaruh Celebrity Endorse Dan Online Customer Review Terhadap Keputusan Pembelian Dengan Kepercayaan Sebagai Variabel Intervening Pada Marketplace Shopee (Studi Pada Konsumen Pengguna Marketplace Shopee Di Kota Langsa) - Haidir, Zul; Chandra, Riny; Amilia, Suri (Movere Journal, 2025)
Abstract: The aim of this research is to determine the influence of celebrity endorsements and online customer reviews on purchasing decisions with consumer trust as an intervening variable (case study of Shopee marketplace users in Langsa City). This research is a quantitative research that uses primary data with a population of Shopee users in Langsa City. The sampling technique used non-probability sampling with a purposive sampling method, the number of respondents was 100 respondents. The data was processed using SPSS for Windows 25, the analysis methods used were the classical assumption test, Sobel test, path analysis and hypothesis testing. Research results: 1) celebrity endorsements influence purchasing decisions, 2) online customer reviews influence purchasing decisions, 3) celebrity endorsements influence trust 4) online customer reviews influence trust, 5) consumer trust cannot mediate celebrity endorsements on purchasing decisions 6) consumer trust can mediate online customer reviews on purchasing decisions, 7) consumer trust influences purchasing decisions Keywords : Celebrity Endorsement, Online Customer Review, Purchase Decision,Trust